Strategi Pengembangan Sumber Daya Manusia Kelompok Usaha Gerabah Tematik Di Kecamatan Dinoyo Kota Malang - MOYO JALADRI, CHAVID; ADI WIJAYA, YULIAN; RACHMAWATY, AYU (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
This research aims to analyze and describe human resource development strategies in the Ceramics business group in Dinoyo District, South Konawe City. The results of this research can be practically useful for developing human resources in the agate business. This research is descriptive. The population and sample in this research were 55 business actors involved in the ceramics business in Dinoyo District, South Konawe City. Data was obtained through interviews and questionnaires. The data analysis technique used is SWOT analysis: strengths, weaknesses, opportunities, and threats. The findings of this research indicate that the appropriate strategy to use in developing human resources in the Ceramics business group in Dinoyo District, South Konawe City, is a divestment strategy whose application is to carry out a selection process for human resource activities such as eliminating the process of making pendants or necklaces because these products are less popular with the public so that these activities can be transferred to a more useful talent development process so that in the future the craftsmen become more developed and creative to produce more varied and innovative ceramic products.